Preservasi Bahan Baku Banten Perspektif Idio-Enviromentalis - Wiradnyana, IBG (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Banten has multi interpretations. It is an essential mean for Hinduism especifically Balinese Hindu. Banten is a dynamic cultural creation in terms of formulation, art apperance as well as materials. Altough banten is created from a dynamic configuration and material but the ideology and spirit ought to be static/firm based on written literature and oral mites.Â Almost all of related manuscripts (literature-source) of Banten instructs that the elements or materials of banten is absolutely depend on the surrounding environment and natural resources. The necessity of the material and others related of banten has fundamentally religious meaning that requires a deep comprehension. The elements, that necessary required have an explicit difination as a sense of devotion, admiring, preserving, developing and exploring the nature resources. As long as Balinese Hindu serves banten for each ritual (panca yadnya â€“ five yajna) on their life means that the ideology Tri Hita Karana (tree harmonius life interaction; Human, Nature God) is being alive as well.Â